Cadaver-specific CT scans visualized at the dissection table combined with virtual dissection tables improve learning performance in general gross anatomy - Paech, Daniel; Giesel, Frederik L.; Kuner, Thomas; Doll, Sara (European radiology, 2016)
ObjectivesThe purpose of this study was to quantify the benefit of the incorporation of radiologic anatomy (RA), in terms of student training in RA seminars, cadaver CT scans and life-size virtual dissection tables on the learning success in general anatomy.MethodsThree groups of a total of 238 students were compared in a multiple choice general anatomy exam during first-year gross anatomy: (1) a group (year 2015, n 1 = 50) that received training in radiologic image interpretation (RA seminar) and additional access to cadaver CT scans (CT + seminar group); (2) a group (2011, n 2 = 90) that was trained in the RA seminar only (RA seminar group); (3) a group (2011, n 3 = 98) without any radiologic image interpretation training (conventional anatomy group). Furthermore, the students’ perception of the new curriculum was assessed qualitatively through a survey.ResultsThe average test score of the CT + seminar group (21.8 ± 5.0) was significantly higher when compared to both the RA seminar group (18.3 ± 5.0) and the conventional anatomy group (17.1 ± 4.7) (p < 0.001).ConclusionsThe incorporation of cadaver CT scans and life-size virtual dissection tables significantly improved the performance of medical students in general gross anatomy. Medical imaging and virtual dissection should therefore be considered to be part of the standard curriculum of gross anatomy.Key Points • Students provided with cadaver CT scans achieved 27 % higher scores in anatomy. • Radiological education integrated into gross anatomy is highly appreciated by medical students. • Simultaneous physical and virtual dissection provide unique conditions to study anatomy.